Factors affect on bioremediation of Co(II) and Pb(II) onto Lonicera japonica flowers powder. Issue 28 (14th June 2016) - Lingamdinne, Lakshmi Prasanna; Koduru, Janardhan Reddy; Jyothi, Rajesh Kumar; Chang, Yoon-Young; Yang, Jae-Kyu
Abstract: Bioremediation is a low-cost eco-friendly separation technique for the treatment of pollutants such as heavy metals and organics from wastewaters. In the present study, a biosorbent, Lonicera japonica flowers powder (LJFP) was prepared from Lonicera japonica flowers (LJF) for treating Pb(II) and Co(II) from aqueous solutions and was well characterized by FT-IR and SEM–EDX. The kinetic results showed that the kinetics of both metal ions was rate limiting pseudo-second order. However, Pb(II) was also involved in chemisorptions, which was proved by the Elovich kinetic model. The equilibrium data of Pb(II) were tuned with Langmuir isotherm whereas Co(II) was fit to Freundlich isotherm model. The maximum uptake capacities of LJFP for Pb(II) and Co(II) were 19.61 and 43.48 mg/g at 298 ± 2 K, pH 6.0. Thermodynamic studies were conducted in the range of temperature, 298–313 ± 2 K, and were revealed that the sorption process of Pb(II) and Co(II) on LJFP was endothermic. Overall studies demonstrated that the biomass, LJFP is a promising, efficient, economical, and reusable sorbent.